Sind Unternehmensplanspiele ein geeignetes Instrument zur Analyse begrenzter Rationalität und tatsächlichen Entscheidungsverhaltens?; Are Business Management Games a Suitable Tool for Analyzing Bounded Rational Behavior of Economic Agents? - Oliver Mußhoff; Norbert Hirschauer; Philipp Hengel (German Journal of Agricultural Economics (GJAE), 2011)
– Regulatory policies often aim to steer the behaviour of economic agents by changing their framework conditions. Assessing the impact of such policies requires forecasts of how humans adapt to changes in their economic environment. A prerequisite for a meaningful policy impact analysis is a profound knowledge why and to what extent economic agents behave in a bounded rational way. We propose that business management games be used to contribute to a better understanding since they provide an inexpensive opportunity to reach beyond the existing anecdotic evidence of "behavioural anomalies". Modifying an existing business management game, in which investment, financing and production decisions have to be made, we demonstrate how bounded rationality can be quantified and separated into its two components: incomplete information and limited cognitive abilities. The resulting data indicate that the decisions made by the participants of the game have been strongly influenced by bounded rationality. They also show that both incomplete information and limited cognitive abilities are relevant components of the bounded rationality that has been displayed by the players. Regulatory impact analysts who base their forecasts a priori on the standard rational choice assumption cause the risk of measures being designed for economic agents that do not exist in reality.
Keywords: 330; Planspiel; Begrenzte Rationalität; Unvollkommene Information; Mathematische Optimierung; Verhaltensökonomik